EVALUASI SALURAN DISTRIBUSI BAWANG MERAH PADA UD WIDJI JAYA DALAM MENINGKATKAN EFEKTIFITAS PEMASARAN DI DESA TEGALARUM - Riangga, Bagas; Nabil, Muhammad; Susanto, Agus (Fakultas Ekonomi dan Bisnis, Universitas Teknologi Sumbawa, 2025)
This study assesses the effectiveness of the shallot distribution channel at UD Widji Jaya in Tegalarum Village, Jaken District, Pati Regency. A qualitative approach with a case study design allows for in-depth analysis of the interactions between distribution actors, price fluctuations, and the length of the marketing chain. The study subjects included UD owners, partner farmers, collectors, and retailers, selected through purposive and snowball sampling. Data were collected through semi-structured interviews, participant observation, and transaction documentation. Data were then analyzed using the Miles and Huberman model, including data reduction, data presentation, and conclusion drawing. The results reveal high price fluctuations and uneven distribution margins, a long distribution chain that reduces market efficiency, and distributors employing adaptation strategies through market diversification and price margin adjustments. The conclusions emphasize the importance of strengthening farmer institutions and utilizing digital distribution to increase transparency, shorten the distribution chain, and create a more efficient, equitable, and sustainable marketing system. These findings contribute to scientific research by highlighting the distribution of risks and adaptation strategies of local actors, which have been understudied in the Indonesian horticultural distribution literature.